2016
DOI: 10.1039/c6dt00929h
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometallated iridium complexes inducing paraptotic cell death like natural products: synthesis, structure and mechanistic aspects

Abstract: Six mononuclear Ir complexes (1-6) using polypyridyl-pyrazine based ligands (L1 and L2) and {[cp*IrCl(μ-Cl)] and [(ppy)Ir(μ-Cl)]} precursors have been synthesised and characterised. Complexes 1-5 have shown potent anticancer activity against various human cancer cell lines (MCF-7, LNCap, Ishikawa, DU145, PC3 and SKOV3) while complex 6 is found to be inactive. Flow cytometry studies have established that cellular accumulation of the complexes lies in the order 2 > 1 > 5 > 4 > 3 > 6 which is in accordance with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 88 publications
5
38
0
Order By: Relevance
“…Poly­(ADP-ribose) polymerase (PARP), for example, is cleaved by caspases during aptoposis . In addition, the protein LC3 is upregulated during the process of autophagy, and ERK is phosphorylated (p-ERK) in paraptosis. , The expression levels of all of these proteins in HeLa cells were evaluated in the presence of complex 13 by Western blots (Figure S34). This compound did not significantly alter the expression levels of any of these proteins, providing evidence against these mechanisms of cell death.…”
Section: Resultsmentioning
confidence: 99%
“…Poly­(ADP-ribose) polymerase (PARP), for example, is cleaved by caspases during aptoposis . In addition, the protein LC3 is upregulated during the process of autophagy, and ERK is phosphorylated (p-ERK) in paraptosis. , The expression levels of all of these proteins in HeLa cells were evaluated in the presence of complex 13 by Western blots (Figure S34). This compound did not significantly alter the expression levels of any of these proteins, providing evidence against these mechanisms of cell death.…”
Section: Resultsmentioning
confidence: 99%
“…Paraptosis has recently been recognized as another non-caspase-dependent type of PCD, as evidenced by the development of endoplasmic reticulum (ER) stress, extensive cytoplasmic vacuolization, and swelling or the dysfunction of the ER and/or mitochondria [7][8][9][10][11]. It has been reported that paraptosis in cancer cells can be induced by viruses [12], metal complexes including copper [13][14][15][16], ruthenium [17,18], titanium [19], iridium [20,21], and rhenium [22], organic compounds such as quinone derivatives [23,24], and naturally occurring compounds such as taxol [25,26], celastrol [27,28], hesperidin [29][30][31], curcumin [32][33][34], gypenoside L [35], morusin [36], chalcomoracin [37], cyclosporine A [38], and ophiobolin A [39]. However, the mechanism responsible for the paraptosis in cancer cells that is induced by these molecules appears to be complicated and has not yet been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In addition, iridium complexes are known to induce selective kinase inhibition property and often display non-apoptotic mode of cancer cell death which are useful for the treatment of resistant cancer. 1,[4][5][6][7][8][9] Moreover, the exciting luminescence properties of iridium complexes are often used as probes for understanding biological processes. In this aspect, a large number of cyclometallated iridium complexes have been developed and studied using various ligand frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…In this aspect, a large number of cyclometallated iridium complexes have been developed and studied using various ligand frameworks. 5,7,8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Among various ancillary ligands, pyridine-based N ∧ N chelating ligands are most promising considering their excellent coordinating ability and stability under physiological condition. 2,4,5,14,18,20,[24][25][26][27][28] Different substituents have been incorporated to N ∧ N donor-based ligands in order to tune the property and activity of the complexes.…”
Section: Introductionmentioning
confidence: 99%